2019
DOI: 10.1093/nar/gkz820
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose)-dependent chromatin unfolding facilitates the association of DNA-binding proteins with DNA at sites of damage

Abstract: The addition of poly(ADP-ribose) (PAR) chains along the chromatin fiber due to PARP1 activity regulates the recruitment of multiple factors to sites of DNA damage. In this manuscript, we investigated how, besides direct binding to PAR, early chromatin unfolding events controlled by PAR signaling contribute to recruitment to DNA lesions. We observed that different DNA-binding, but not histone-binding, domains accumulate at damaged chromatin in a PAR-dependent manner, and that this recruitment correlates with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 75 publications
(115 reference statements)
3
54
0
Order By: Relevance
“…However, it was also shown that PARylation of histones and the respective damage sites results in chromatin remodelling and relaxation of the chromatin structure. Resulting from this, accessibility of the damage site is improved and binding of DNA repair factors enhanced upon PARylation [ 33 , 57 ]. Thus, the negative relationship we observed could also reflect a repair facilitating effect of PARylation concomitant with decreasing DNA damage levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was also shown that PARylation of histones and the respective damage sites results in chromatin remodelling and relaxation of the chromatin structure. Resulting from this, accessibility of the damage site is improved and binding of DNA repair factors enhanced upon PARylation [ 33 , 57 ]. Thus, the negative relationship we observed could also reflect a repair facilitating effect of PARylation concomitant with decreasing DNA damage levels.…”
Section: Discussionmentioning
confidence: 99%
“…Design of oligonucleotides was based on a previously suggested base sequence harbouring the DNA lesion 8-oxodG [ 12 ]. In addition, this base sequence was shown to be suitable for investigation of incision activity towards an AP site analogue (tetrahydrofuran (THF) derivate) [ 57 ]. THF is commonly applied to mimic an AP site in oligonucleotides [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…To confirm that PARP1 is trapped on DNA upon Ews siRNA depletion, we stably expressed GFP‐PARP1 in U2OS cells and precisely monitored the kinetics of GFP‐PARP1 after micro‐irradiation (Smith et al , 2019). We found that while GFP‐PARP1 equally accumulated on micro‐irradiated sites both in WT and Ews −/− cells, it persisted longer when EWS was depleted (Fig 2C).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, they have been used to discriminate the recruitment of DNA repair proteins at damaged sites in heterochromatin vs. euchromatin regions: light-stimulated production of oxidatively generated DNA lesions was obtained with Killer Red protein fused to transcription repressor, or activator cassettes integrated into distinct genomic loci [87]. Lastly, the chromatin unfolding effect induced by PARP-1 on the accessibility of DNA-binding vs. histone binding domains to DNA damage sites has been investigated by live-cell imaging and fluorescence lifetime measurements [88].…”
Section: In Situ Detection Of Dna-protein Complex Formationmentioning
confidence: 99%